Results of combination treatment using docetaxel in an adjuvant chemotherapy regimen for resectable breast cancer - L. V. Bolotina; T. I. Deshkina (Опухоли женской репродуктивной системы)
Breast cancer (BC) dominates in the structure of cancer morbidity and mortality in women worldwide. Despite the advances made in the treatment of this pathology, there is still a variety of unsolved problems, including those associated with disease progression after radical sur- gical interventions. One of the urgent current tasks is to estimate the adequate volume of adjuvant treatment with regard to the biological features of a tumor. Our investigation comparatively analyzed the efficiency of two adjuvant chemotherapy regimens (AT and FAC) in patients with primary operable BC in relation to the immunohistochemical tumor subtype (luminal B, luminal HER, HER-2-positive and triple- negative) and the extent of the disease (N0, N1 and N2–3).